2021
DOI: 10.1101/2021.08.23.21256078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survivors of SARS-CoV-2 Infection Show Neuropsychiatric Sequelae Measured by Surveys, Neurocognitive Testing, and Magnetic Resonance Imaging: Preliminary Results

Abstract: A significant number of individuals experience physical, cognitive, and mental health symptoms in the months after acute infection with SARS-CoV-2, the virus that causes COVID-19. This study assessed depressive and anxious symptoms, cognition, and brain structure and function in participants with symptomatic COVID-19 confirmed by PCR testing (n=100) approximately three months following infection, leveraging self-report questionnaires, objective neurocognitive testing, and structural and functional neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A prospective cohort study from the US assessed neurologic symptoms among 100 participants with standardized questionnaires, cognitive tests, and brain scans. 31 Early results from the study reported 2 clusters of neurocognitive impairment. 31 One cluster had people with symptoms affecting all neurocognitive domains, whereas the other cluster had a milder impact limited to people's attention.…”
Section: Author (Year) Country Study Population Major Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…A prospective cohort study from the US assessed neurologic symptoms among 100 participants with standardized questionnaires, cognitive tests, and brain scans. 31 Early results from the study reported 2 clusters of neurocognitive impairment. 31 One cluster had people with symptoms affecting all neurocognitive domains, whereas the other cluster had a milder impact limited to people's attention.…”
Section: Author (Year) Country Study Population Major Findingsmentioning
confidence: 98%
“…31 Early results from the study reported 2 clusters of neurocognitive impairment. 31 One cluster had people with symptoms affecting all neurocognitive domains, whereas the other cluster had a milder impact limited to people's attention. 31 Brain imaging results also revealed that people who reported experiencing anosmia -the loss of sense of smell -had structural neurologic differences compared to those who did not report anosmia.…”
Section: Author (Year) Country Study Population Major Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…In five additional subjects, we analyzed data from a typical resting state fMRI study (Hack et al, 2021) where PPG signals were acquired. A whole brain EPI sequence was used with 3mm isotropic voxels, a flip angle of 77 degrees, TR = 2s, TE = 27.5ms, FOV = 216x216 and 45 slices.…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%
“…In order to understand whether the characteristic blood and CSF pulsations could also be observed with a typical resting state fMRI scan, we analyze data from 5 subjects who were scanned in a different project (Hack et al, 2021). In these resting state scans, the echo time is slower and the repetition time is slower (SMS: TE = 11.6ms, FA = 48, TR = 250ms, resting state fMRI: TE = 27.5ms, FA = 77, TR = 2000ms), but each slice is still acquired within a short time of 44.4 ms. Each slice can be aligned to the PPG peak, and cardiac pulsations can be extracted.…”
Section: Cardiac-gated Resting Statementioning
confidence: 99%